Infrastructure of the agricultural consulting in the Republic of Kazakhstan: experiences for Ukraine - Похиленко, Н. М. (Scientific Progress & Innovations, 2012)
The results of the study concerning the conditions and experiences of the formation and organization of the spreading system of agricultural knowledge and information in the Republic of Kazakhstan have been given. The structure of consulting support of the agriculture producers in accordance with information and advice, analytical marketing, information technologies and exhibition and fair activities has been considered. The conditions of the development of spreading system of agricultural knowledge and information in the Republic of Kazakhstan with the possible adaptation to the conditions of Ukraine have been generalized.